Analisis Yuridis Pertanggungjawaban Pidana Terhadap Anak Sebagai Pelaku Tindak Pidana Penyalahgunaan Narkotika (Studi Penetapan Nomor. 22/Pid.Sus- Anak/2016/Pn.DPS) - Utari Paramita Devi; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Preferensi Hukum, 2021)
Currently, Indonesia is in a state of emergency on drugs because its abuse is widespread in society, starting from size, class, and age. Drug abuse is not only done by the adult class but also by minors, it damages the mental and soul of the generation. The Indonesian government has passed a law related to the protection of minors who are victims of Narcotics abuse based on Law no. 35/2014 on PA. This study examines criminal sanctions against criminal acts of child participation as narcotics abuse and analyzes judges' considerations in deciding cases in determining sanctions based on Number. 22 / Pid.Sus Anak / 2016 / PN Dps. This study employed normative research, with a statutory perspective. Sources of data were primary and secondary legal materials obtained through interviews, reading, and examining legal theories related to the problem being researched. After all, data was collected, it was analyzed descriptively qualitatively. The results of the research showed that the criminal sanctions imposed on the involvement of children as drug abusers must be aimed at improving themselves, and the judge's consideration in deciding this case was by taking into account the provisions of Article 12, Article 52 paragraph 5 of Law no. 11/2012 concerning SPPA.